Essays on structural change and social integration - Ivanov, Boris (2023)
The present dissertation studies the role of job loss during times of structural change and how policy interventions can improve the well-being of unemployed individuals. The first chapter explores how local labor market conditions and job loss interact to shape the careers of workers in declining manufacturing occupations. The second chapter examines how workers are affected if they lose their job after the task requirements of their occupation have changed. The results show that the income and employment losses of displaced workers vary strongly across occupations and regions: If a worker’s prior occupation is locally declining or has strongly changed its task requirements, job loss has a much more negative impact on individual careers. The third chapter evaluates whether subsidized jobs can improve the social integration and well-being of unemployed workers with little access to regular jobs. It shows that well-designed and targeted public employment schemes can substantially improve the social integration of these individuals, while the additional costs are limited. As a common feature, these chapters study what determines the costs of job loss for individual workers. The first two chapters focus on the economic costs of job loss during structural transformation. The third chapter takes a different angle by considering the psychosocial costs of unemployment and whether public policy measures can help to ease them.